2021
DOI: 10.3389/fimmu.2021.621706
|View full text |Cite
|
Sign up to set email alerts
|

Immunoinformatics Design of Multi-Epitope Peptide-Based Vaccine Against Schistosoma mansoni Using Transmembrane Proteins as a Target

Abstract: Schistosomiasis remains a serious health issue nowadays for an estimated one billion people in 79 countries around the world. Great efforts have been made to identify good vaccine candidates during the last decades, but only three molecules reached clinical trials so far. The reverse vaccinology approach has become an attractive option for vaccine design, especially regarding parasites like Schistosoma spp. that present limitations for culture maintenance. This strategy also has prompted the construction of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 84 publications
5
64
0
Order By: Relevance
“…Multi epitope vaccines could induce a wide range of immune responses because of the presence of B cell and T cell epitopes. Therefore, the study of epitopes has played an important role in the construction of E. granulosus vaccines [16,17]. The results of the present study indicated that the amino acid sequence of EGR-03347 included 11 potential B cell linear epitopes, which suggested that EGR-03347 has great antigenic potential.…”
Section: Discussionmentioning
confidence: 69%
“…Multi epitope vaccines could induce a wide range of immune responses because of the presence of B cell and T cell epitopes. Therefore, the study of epitopes has played an important role in the construction of E. granulosus vaccines [16,17]. The results of the present study indicated that the amino acid sequence of EGR-03347 included 11 potential B cell linear epitopes, which suggested that EGR-03347 has great antigenic potential.…”
Section: Discussionmentioning
confidence: 69%
“…Although some multi-epitope vaccines against Schistosoma have been reported [ 104 , 121 , 122 ], the MEV developed in this work exhibits outstanding properties because it uses the core proteome of three Schistosoma species that primarily affects humans. As the constructed vaccine contains an adjuvant, B cell, and T cell epitopes (CTL, HTL), it can promote innate and adjuvant immunological reactions in the host body, making it an excellent and suitable candidate for Schistosoma vaccine production.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed recombinant polypeptide vaccine is the product of a peptide screening process combining both immunoinformatics and in vitro assays. In recent years, the fields of genomics and bioinformatics have evolved to enable computational screening of epitopes considering a diversity of HLAs [60]. The reliability of such methods can be increased by analyzing the results from multiple prediction tools.…”
Section: Discussionmentioning
confidence: 99%